2012
DOI: 10.1186/1472-6963-12-483
|View full text |Cite
|
Sign up to set email alerts
|

A new analytical framework of 'continuum of prevention and care' to maximize HIV case detection and retention in care in Vietnam

Abstract: BackgroundThe global initiative ‘Treatment 2.0’ calls for expanding the evidence base of optimal HIV service delivery models to maximize HIV case detection and retention in care. However limited systematic assessment has been conducted in countries with concentrated HIV epidemic. We aimed to assess HIV service availability and service connectedness in Vietnam.MethodsWe developed a new analytical framework of the continuum of prevention and care (COPC). Using the framework, we examined HIV service delivery in V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…23 First, HTC uptake is very limited among key populations, with only 31% of IDU, 40% of female SWs and 39% of MSM reported that they had received HTC in the past 12 months and knew their test results in 2012 (Table 2). 69 An analysis of the new HIV diagnosis and the clinic enrolment data at national 70 and provincial levels 70 suggests that a substantial number of people diagnosed with HIV infection are lost to follow-up and are not effectively linked to care. People are also starting ART late, 70,71 with a median CD4 count of 93 cells mm -3 in 2010, associated with a higher attrition rate.…”
Section: Challenges and Opportunities For Art-based Prevention In Viementioning
confidence: 99%
See 3 more Smart Citations
“…23 First, HTC uptake is very limited among key populations, with only 31% of IDU, 40% of female SWs and 39% of MSM reported that they had received HTC in the past 12 months and knew their test results in 2012 (Table 2). 69 An analysis of the new HIV diagnosis and the clinic enrolment data at national 70 and provincial levels 70 suggests that a substantial number of people diagnosed with HIV infection are lost to follow-up and are not effectively linked to care. People are also starting ART late, 70,71 with a median CD4 count of 93 cells mm -3 in 2010, associated with a higher attrition rate.…”
Section: Challenges and Opportunities For Art-based Prevention In Viementioning
confidence: 99%
“…69 An analysis of the new HIV diagnosis and the clinic enrolment data at national 70 and provincial levels 70 suggests that a substantial number of people diagnosed with HIV infection are lost to follow-up and are not effectively linked to care. People are also starting ART late, 70,71 with a median CD4 count of 93 cells mm -3 in 2010, associated with a higher attrition rate. 72 Attrition was defined as discontinuation of ART due to death or loss to follow-up, or discontinuation of ART medications while remaining in care.…”
Section: Challenges and Opportunities For Art-based Prevention In Viementioning
confidence: 99%
See 2 more Smart Citations
“…In 2014, the Joint United Nations Program on HIV/ AIDS released goals for HIV engagement and treatment by 2020: that 90% of all people living with HIV will know their status; 90% of all people diagnosed with HIV will receive antiretroviral therapy; and 90% of those on antiretroviral therapy will be virally suppressed [4]. Recent literature highlights systems-level factors that impact this care continuum in Vietnam, including the cost of treatment [5], care coordination, chronic disease management, and peer networks [6]. However, little is known about patient level factors that contribute to engaging in the HIV care continuum in Vietnam.…”
Section: Introductionmentioning
confidence: 99%